(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Methicillin resistant Staphylococcus aureus (MRSA) is a Gram positive bacterium and is frequent cause of infections worldwide. It is resistant to a large group of antibiotics called beta-lactams. The objective of our study was to determine the prevalence of MRSA and to assess its current antibiotic susceptibility pattern. The study was conducted in June, 2014 to November 2014 and 100 cases of staphylococcus positive were selected for this study. The 56% of isolates were from male and 44% were from female patients. Out of 100 isolates of S. aureus 53% were Methicillin resistant. Most of the MSRA specimens were found to be susceptible to vancomycin, whereas most were resistant to ampicillin and cephradin. MSRA isolates were 69% in hospitalized patients and majority was isolated from pus (67%), followed by from sputum samples (21%). The study concluded that to curb the occurrence of MSRA, continuous monitoring of hospital acquired infections and surveillance of antibiotic susceptibility pattern is essential. Proper detection of all MSRA with accurate and quick assays must be adopted as a routine laboratory procedure.